2020
DOI: 10.1016/j.mehy.2020.110305
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in children: Could pertussis vaccine play the protective role?

Abstract: While COVID-19 continues to spread across the globe, diligent efforts are made to understand its attributes and dynamics to help develop treatment and prevention measures. The paradox pertaining to children being the least affected by severe illness poses exciting opportunities to investigate potential protective factors. In this paper, we propose that childhood vaccination against pertussis (whooping cough) might play a non-specific protective role against COVID-19 through heterologous adaptive responses in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The results reported here add to the literature reviewed in the Introduction that cast doubt on studies reporting that BCG, polio, or DPT vaccinations may protect against COVID-19 acquisition or death [64][65][66][67][68][69][70][71][72][73][74][75][76]. However, one important caveat must be mentioned, which is that it was not possible in this study to differentiate between nations using acellular pertussis vaccines, those using whole-cell pertussis vaccines, and those using both as part of their vaccination programs.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results reported here add to the literature reviewed in the Introduction that cast doubt on studies reporting that BCG, polio, or DPT vaccinations may protect against COVID-19 acquisition or death [64][65][66][67][68][69][70][71][72][73][74][75][76]. However, one important caveat must be mentioned, which is that it was not possible in this study to differentiate between nations using acellular pertussis vaccines, those using whole-cell pertussis vaccines, and those using both as part of their vaccination programs.…”
Section: Discussionmentioning
confidence: 71%
“…Finally, diphtheria-tetanus-pertussis vaccination [ 74 , 75 , 76 , 77 ] and polio vaccination [ 78 ] have also been suggested as possible prophylactics against COVID-19, but at present, no ecological study exists to support these possibilities. Published studies have found no protective benefit [ 5 , 44 , 45 ], and antibody titers against tetanus do not correlate with COVID-19 protection [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tuberculosis vaccine Baccilus Calmette-Guérin (BCG) has been studied in this context, as it is known to generally boost the innate immune response and reduce respiratory tract infections ( 9 ), with some studies finding a relation between BCG national vaccination programs and COVID-19 mortality rates ( 10 ), although there have also been studies that have discarded the protective effects of BCG vaccinations ( 11 ). Several other vaccines may ready the immune response with partial specificity, and thereby produce protective effects ( 12 14 ). Indeed, there appear to be sequence similarities between proteins in pathogens targeted by common vaccines and SARS-CoV-2 ( 14 16 ); e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Others argue that whooping cough is a vaccine-preventable infectious disease of the airways and shares many similarities with COVID-19, including transmission mode and clinical features. Although pertussis is caused by a bacterium ( Bordetella pertussis ) while COVID-19 is a viral infection (SARS-CoV-2), some data seem to support that cross-reactivity and heterologous adaptive responses can also be observed among unrelated agents such as between bacteria and viruses [ 32 ].…”
Section: Possible Correlation Between Vaccinations and Covid-19: Rmentioning
confidence: 99%